Lithium-Sulfur Batteries: Current Achievements and Further Development - Kaskel, Stefan; Huang, Jia-Qi; Sakaebe, Hikari (Batteries & Supercaps, 2022)
In this Editorial, Guest Editors Stefan Kaskel, Jia-Qi Huang, and Hikari Sakaebe introduce the Special Collection of Batteries & Supercaps on Lithium–Sulfur batteries. They discuss the challenges that lithium-ion batteries currently face and how they can be solved using lithium-sulfur batteries using various interesting approaches from scientists around the world.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrolytes; lithium-sulfur batteries; metal composites; structural characterization; sulfur host materials